Syphilis, human immunodeficiency virus, herpes genital and hepatitis B in a women's prison in Cochabamba, Bolivia: prevalence and risk factors - M Villarroel-Torrico; K Montaño; P Flores-Arispe; E Jeannot; A Flores-León; N Cossio; C Valencia-Rivero; A Salcedo-Meneses; M Jiménez-Velasco; R Castro-Soto; G Gétaz-Jiménez; H Bermúdez-Paredes; et al. (Sociedad Española de Sanidad Penitenciaria, 2018)
ABSTRACT Objective To determine the prevalence and factors associated with syphilis, human immunodeficiency virus (HIV), hepatitis B (HBV) and herpes type 2 (HSV2) among women in the prison of San Sebastian in Cochabamba (Bolivia). Material and methods We carried out a cross-sectional study including a standardized questionnaire to assess socio-demographics characteristics and risk factors (sexual practices and exposure to blood); and serological tests for syphilis, HSV2, VIH, and HBV. We performed bivariate and multivariate analyses to test the associations between variables of interest and infections. Results A total of 219 out of 220 prisoners (99.5%) participated in the study. For syphilis, 12.8% of participants had both reactive tests (RPR+/TPPA+). The prevalence of HSV2 and VIH was 62.6% and 1.4%, respectively. Anti-HBc, indicating a resolved or chronic HBV, was positive in 11.9% of participants and 0.5% had active HBV (HBsAg positive). A low level of education was associated with syphilis, HSV2 and HBV. Having occasional sexual partners was associated with syphilis and HSV2. Being over 36 years old and having more than 3 children were associated with HBV. The number of sexual partners, history of prostitution and rape, having sexual intercourses in prison and detention time were not associated with any of these infections. Discussion The prevalence of syphilis, HIV, HSV2 and HBV was higher in this vulnerable female population than in the general population in Bolivia. Control measures in detention are needed to limit the spread of these infections both in prisons and in the community.